Marketing in the public sector—benefits and barriers: a bibliometric study from 1931 to 2020 - Matos, Nelson (2020)
The global economy has brought economic and social changes that have led organizations to extend their vision beyond consumer and business markets. Particularly, in the marketing of public sector (MPS), the extant theoretical foundations require more comprehensive investigations not only into the main topics researchers have looked into the past, but also into the new challenges they will face in the future. Thus, the purpose of this study is to provide a thorough a bibliometric overview of the theoretical framework and to identify benefits and barriers of marketing in the public sector. We provide an overview of the theoretical framework and identify the benefits and barriers of marketing in the public sector through a bibliometric study. To achieve this objective, a systematic literature review was conducted of 3926 articles from 1931 to 2020. The results allowed the identification of four main theoretical clusters: educational, public health, social economics and urban politics. It also offered benefits and barriers in the context of MPS. Conclusions and implications to the academia and managers are drawn. Future research opportunities are also provided.